2019
DOI: 10.1111/jfbc.12764
|View full text |Cite
|
Sign up to set email alerts
|

Raffia palm (Raphia hookeri) wine extenuates redox imbalance and modulates activities of glycolytic and cholinergic enzymes in hyperglycemia-induced testicular injury in type 2 diabetic rats

Abstract: This study investigated the effects of Raffia palm wine (RPW) on redox imbalance, glycolytic and cholinergic enzymes, and ATPase activities in hyperglycemia‐induced oxidative testicular injury. Type 2 diabetes (T2D) was induced in male albino rats (Sprague‐Dawley) by first administering 10% fructose solution for 14 days, before injecting with an intraperitoneal injection (40 mg/kg body weight) of streptozotocin. Raffia palm wine was administered to two diabetic groups at 150 and 300 mg/kg body weight (bw), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In this study, the therapeutic effect of the BCAA, l-leucine was investigated on oxidative testicular injury. Oxidative stress has been implicated in the dysfunction of the male reproductive system, which has been attributed to the high susceptibility of the testicular polyunsaturated fatty acids (PUFAs) to free radical attack (Erukainure et al 2019b;Obode et al 2015). The depleted GSH and non-protein thiol levels, SOD and catalase activities in the untreated tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the therapeutic effect of the BCAA, l-leucine was investigated on oxidative testicular injury. Oxidative stress has been implicated in the dysfunction of the male reproductive system, which has been attributed to the high susceptibility of the testicular polyunsaturated fatty acids (PUFAs) to free radical attack (Erukainure et al 2019b;Obode et al 2015). The depleted GSH and non-protein thiol levels, SOD and catalase activities in the untreated tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been recognized as one of the main stimuli that triggers the pathogenesis and progression of testicular dysfunction (Erukainure et al 2019b). This can be attributed to the high concentration of unsaturated fatty acids in the testes and sperm cells, which are susceptible to peroxidative damage (Aitken and Roman 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Erukainure, Reddy, and Islam (2019) reported that Raffia palm wine inhibited glycogen phosphorylase, glucose‐6‐phosphatase, fructose‐1,6‐bisphosphatase, and acetylcholinesterase. Raffia palm wine had the therapeutic potentials against the effects of hyperglycemia‐induced oxidative testicular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance occurs when excess glucose in the blood reduces the ability of the cells to absorb and use blood sugar for energy. Thus, the pancreas makes more insulin to overcome the low rate of absorption and keep blood sugar levels down (Erukainure et al, 2019). Mei et al (2016) reported that Phlorizin administration prevented the increases of fasting serum insulin concentration and HOMA‐IR in db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…The nitric oxide (NO) concentration was determined with Griess method of Erukainure et al. (2019) and Tsikas (2005). Briefly, 100 μl of testes supernatant or blank (distilled water) was added to 100 ml of Griess reagent and incubated for 30 min at 25°C in a dark chamber.…”
Section: Methodsmentioning
confidence: 99%